THE ROLE OF THE DIRECT METHOD IN ENGLISH LANGUAGE LEARNING - Aysulu Imamatdinovna Karamatdinova; Dilfuza Khudaykul kizi Iskandarova (PEDAGOGS, 2025)
Abstract: A language teaching strategy known as the Direct method emphasizes speaking the target language directly and without translation. By focusing on oral communication and deep learning, this approach improves students’ comprehension, pronunciation, and fluency. This study examines the effects of the "Direct" approach to teaching English on students’ overall language acquisition and speaking skills. According to a mixed-method approach that includes surveys and interviews with English language learners, although practice poses challenges for students who have difficulty remembering terms, it significantly increases speaking confidence and listening skills. According to the results, vocabulary building techniques should be used in addition to the "Direct method", which is very useful for improving communicative skills.